2011
DOI: 10.1007/s00467-011-1761-9
|View full text |Cite
|
Sign up to set email alerts
|

Pseudodominant inheritance of nephronophthisis caused by a homozygous NPHP1 deletion

Abstract: Nephronophthisis (NPHP) is an autosomal recessive kidney disease characterized by tubular basement membrane disruption, interstitial infiltration, and tubular cysts. NPHP leads to end-stage renal failure in the first two decades of life and is the most frequent genetic cause of chronic renal failure in children and young adults. Mutations in eleven genes (NPHP1-11) have been identified. Extrarenal manifestations are known, such as retinitis pigmentosa (Senior-Løken syndrome, SLS), brainstem and cerebellar anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…The genetic analyses in our adult‐onset patient revealed a homozygous full gene deletion of NPHP1 , which is typically associated with juvenile nephronophthisis . Albeit rare, other similar patients of NPHP‐induced delayed/adult‐onset ESRD have previously been observed . More recently, 26 (0.5%) patients harboring a homozygous NPHP1 full gene deletion were identified among 5606 patients that underwent kidney transplantation .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The genetic analyses in our adult‐onset patient revealed a homozygous full gene deletion of NPHP1 , which is typically associated with juvenile nephronophthisis . Albeit rare, other similar patients of NPHP‐induced delayed/adult‐onset ESRD have previously been observed . More recently, 26 (0.5%) patients harboring a homozygous NPHP1 full gene deletion were identified among 5606 patients that underwent kidney transplantation .…”
Section: Discussionmentioning
confidence: 59%
“…3,4,8,9 Albeit rare, other similar patients of NPHP-induced delayed/adult-onset ESRD have previously been observed. [10][11][12][13] More recently, 26 (0.5%) patients harboring a homozygous NPHP1 full gene deletion were identified among 5606 patients that underwent kidney transplantation. 5 The average age at which these patients developed ESRD was 30 years (range, 18-61 years), and 54% of the patients were aged greater than 30 years at ESRD onset.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients had hematuria. In another report, a Turkish family with pseudodominant inheritance of nephronophthisis in two generations, suggestive of an autosomal dominant inheritance, was described [17], however haplotype analysis revealed distant relationship between the parents of all patients, despite the family pedigree indicating no obvious consanguinity in the last three generations. In this family, the causing molecular defect was a recurrent NPHP1 gene deletion.…”
Section: Discussionmentioning
confidence: 95%
“…In adults, clinical and radiological symptoms of nephronophthisis might be unspecific that makes the diagnosis very difficult [17]. It is important for physicians to consider nephronophthisis as one possible diagnosis in adult patients with features of chronic tubulointerstitial nephropathy even in presence of an elevated serum uric acid concentration that usually leads to screen UMOD gene.…”
Section: Discussionmentioning
confidence: 99%
“…Georges et al [17] described 4 NPHP-RC patients (Senior-Løken syndrome) who progressed to ESKD between the ages of 42 and 56 years. Hoefele et al [18] described a patient with NPHP1 deletion who was affected by ESKD at 43 years. Halbritter et al [15] reported 2 NPHP-RC patients with IQCB1 compound heterozygous mutations; they were affected by ESKD at 51 and 43 years.…”
Section: Discussionmentioning
confidence: 99%